FREQUENCY AND SEVERITY OF PERIODONTAL DISEASE IN CANINE PATIENTS OF A PET CLINIC IN LIMA CITY - Maetahara R., Arturo (2010)
The frequency of periodontal disease was evaluated in 52 canines older than one year of age, patients of the Small Animal Clinic, School of Veterinary Medicine of San Marcos University, Lima, during the period of October 2005 to March 2006. The veterinary periodontal index was used. The results showed a frequency of 76.9% (40/52) of dogs with periodontal disease, where 48.1% (25/52) had gingivitis, 21.2% (11/52) mild periodontitis, and 7.7% (4/52) moderate periodontitis. The more affected type of teeth was the premolars and the superior teeth. There was a positive association between age with frequency and severity of periodontal disease. It was also observed that missing teeth was higher in older dogs.